(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
It has been hypothesized that the change in the micro and macro geometry of the grinding wheel can be determined by a non-contact way by supplying jet of air through the nozzle of a pneumatic-electric-contact converter to the surface of the tool during operation. To confirm this hypothesis an experiment was did on a surface grinding machine. Various samples were machined, that led to self-sharpening of the tool. Grinding wheel monitoring system was developed for the experiments. System includes a device that provides the setting of the necessary working gap between the nozzle and the controlled wheel. A justification is proposed for determining the frequency of grinding wheel grinding during operation by accurately accounting for changes in the state of its surface without stopping the machining process.